2022
DOI: 10.1021/acs.jctc.2c01111
|View full text |Cite
|
Sign up to set email alerts
|

Ground- and Excited-State Dipole Moments and Oscillator Strengths of Full Configuration Interaction Quality

Abstract: We report ground-and excited-state dipole moments and oscillator strengths (computed in different "gauges" or representations) of full configuration interaction (FCI) quality using the selected configuration interaction method known as Configuration Interaction using a Perturbative Selection made Iteratively (CIPSI). Thanks to a set encompassing 35 ground-and excited-state properties computed in 11 small molecules, the present near-FCI estimates allow us to assess the accuracy of high-order coupled-cluster (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 180 publications
0
24
0
Order By: Relevance
“…The CI derivatives are (35) With these source terms, the Z-vector equation for ASCI-SCF is solved to obtain the effective densities as (36) (37) (38) where (39) (40)…”
Section: Iiii Sa-asci-scf and Sa-asci-scf-pt2mentioning
confidence: 99%
See 1 more Smart Citation
“…The CI derivatives are (35) With these source terms, the Z-vector equation for ASCI-SCF is solved to obtain the effective densities as (36) (37) (38) where (39) (40)…”
Section: Iiii Sa-asci-scf and Sa-asci-scf-pt2mentioning
confidence: 99%
“…Indeed, the first implementation of ASCI showed that the excited state is well described . Recently, the dipole moments and oscillator strengths are shown to be reliably described with the configuration interaction using a perturbative selection made iteratively (CIPSI) method . Naturally, if the ASCI formalism accurately approximates the FCI excited states, then the state-averaged ASCI-SCF (SA-ASCI-SCF) should resemble the SA-CASSCF states as well.…”
Section: Introductionmentioning
confidence: 99%
“…Selected configuration interaction (SCI) 19 -based approaches have been recently used to calculate accurate estimates for vertical excitation energies, 20−23 double excitations, 13 doublet− doublet transitions in radicals, 24 and excited-state dipole moments and oscillator strengths. 25 relatively small subspace of determinants, SCI techniques attempt a bottom-up discovery of this space of "important" Slater determinants. For weakly correlated systems, SCI provides an incredibly efficient approach for obtaining near-FCI estimates of the ground and excitated state energies.…”
Section: Introductionmentioning
confidence: 99%
“…Selected configuration interaction (SCI)-based approaches have been recently used to calculate accurate estimates for vertical excitation energies, double excitations, doublet–doublet transitions in radicals, and excited-state dipole moments and oscillator strengths . Motivated by the fact that low-energy eigenstates often have most of their weight on a relatively small subspace of determinants, SCI techniques attempt a bottom-up discovery of this space of “important” Slater determinants.…”
Section: Introductionmentioning
confidence: 99%
“…It does not require an active space to be chosen, so it removes the requirement of expertise and the possibility of bias. Selected CI initially used perturbation estimates of a configuration’s significance, and recently, there has been much successful research into going beyond this approach, which includes refs . Those works have demonstrated that selected CI can be particularly useful for multireference problems, where small corrections to a single determinant can perform poorly.…”
Section: Introductionmentioning
confidence: 99%